Coprodução de biogás e biofertilizante por biodigestão anaeróbica de cama de aviário - Fernandes, Juliana Aparecida Corrêa da Silva (2022)
The search for ways to use solid waste generated in agricultural production has been intense and, especially in poultry, the poultry litter after use can be reused in the anaerobic biodigestion process, generating biogas, renewable energy source, in addition to digestate, or biofertilizer ̶ solid resulting from the conversion of biomass into biogas. Biogas can be used to supply equipment on the property or sold, if it undergoes a refining process to remove impurities. Thus, it is expected to reduce costs with electricity supplied by the concessionaire, or due to the lower consumption of firewood. This study aims to carry out the process of anaerobic biodigestion of saturated poultry litter, used by 6 batches, subject to disposal. The controlled biodigestion of residual biomass was carried out in a handcrafted prototype biodigester, the biogas production was monitored during the experiment and the chemical characterization of the poultry litter was carried out before and after the biodigestion process to evaluate the technical feasibility of the biofertilizer produced. Biogas production was monitored and economic aspects were projected.